A PURPOSED ADVISORY MODEL FOR ACTIVITY CONDUCTION AND EVALUATION OF ANALYTICAL THINKING IN READING AND WRITING OF TEACHERS IN EXPANDING EDUCATIONAL OPPORTUNITY SCHOOLS IN THE UPPER NORTHERN AREA - กอบกำ, เอกฐสิทธิ์ (Ganesha Journal, 2017)
The state of activity conduction and evaluation of reading critical thinking and writing of teachers in Expanding Educational Opportunity Schools in the Upper Northern Area in overall, according to the teachers and educational supervisors, It showed that the performance was rated at a medium level. For statistical comparison by using t-test, it did not show any difference at significance of .01. teachers and educational supervisors needed a clear-cut and a practical model. 2. The model of Supervision for Activity Conduction and Evaluation of Reading, Critical Thinking and Writing of Teachers in Expanding Educational Opportunity Schools in the Upper Northern Area was called APICE Model, it was a model which was reasonable, practical and consistent according to the theories. Results of using APICE Model were as follows: 3.1 After using the model, the teachers who were under supervision had knowledge an understanding on activity conduction and evaluation of reading, critical thinking and writing at higher level than before. When comparing to the control-group teachers, it was found that there was a different of knowledge and understanding of those activities. 3.2 The teachers, who had undergone the above-mentioned supervision, Model had been able to conduct those activities and evaluation at a high level. Their satisfaction towards the model was at the highest level. 3.3 For the students of Expanding Educational Opportunity Schools in the Upper Northern Area, after using the Educational Supervision Model, the results of their literacy and reasoning ability were at higher level than before at the statistical significance of 01.